2018
DOI: 10.1038/s41388-018-0473-z
|View full text |Cite
|
Sign up to set email alerts
|

EGF-induced nuclear localization of SHCBP1 activates β-catenin signaling and promotes cancer progression

Abstract: Aberrant activation of EGFR represents a common event in non-small cell lung carcinoma (NSCLC) and activates various downstream signaling pathways. While EGFR activation of β-catenin signaling was previously reported, the mediating mechanism remains unclear. Our current study found that EGFR activation in NSCLC cells releases SHC-binging protein 1 (SHCBP1) from SHC adaptor protein 1 (SHC1), which subsequently translocates into the nucleus and directly promotes the transactivating activity of β-catenin, consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 60 publications
4
59
0
Order By: Relevance
“…The protein interaction network identified nine key genes [RAD51 (29), KIF4A (30), RACGAP1 (31), SPAG5 (32), HMMr (33), cdc25c (34), cKS2 (35), SHcBP1 (36) and ERCC6L (37)] that interacted strongly with CENPM mRNA. Subsequently, the functions of these nine genes (38)(39)(40)(41)(42)(43)(44)(45)(46) were profiled in various types of cancer and it was identified that all of them have been reported to accelerate the progression of cancer, including BC and hepatocellular carcinoma (29)(30)(31)(32)(33)(34)(35)(36)(37). RT-qPCR demonstrated that the expression levels of five of the nine genes, ERCC6L, CKS2, KIF4A, SPAG5 and CDC25C, were increased in MCF7 cells with elevated CENPM expression, implying that cenPM may promote tumor progression by controlling the expression of these five genes.…”
Section: Discussionmentioning
confidence: 99%
“…The protein interaction network identified nine key genes [RAD51 (29), KIF4A (30), RACGAP1 (31), SPAG5 (32), HMMr (33), cdc25c (34), cKS2 (35), SHcBP1 (36) and ERCC6L (37)] that interacted strongly with CENPM mRNA. Subsequently, the functions of these nine genes (38)(39)(40)(41)(42)(43)(44)(45)(46) were profiled in various types of cancer and it was identified that all of them have been reported to accelerate the progression of cancer, including BC and hepatocellular carcinoma (29)(30)(31)(32)(33)(34)(35)(36)(37). RT-qPCR demonstrated that the expression levels of five of the nine genes, ERCC6L, CKS2, KIF4A, SPAG5 and CDC25C, were increased in MCF7 cells with elevated CENPM expression, implying that cenPM may promote tumor progression by controlling the expression of these five genes.…”
Section: Discussionmentioning
confidence: 99%
“…21 More recently, PRMT5 was demonstrated that lead to FBW7 expression to promote tumorigenesis in pancreatic cancer. 14 ling, 24 and EGF-induced nuclear translocation of SHCBP1 directly increased acetylation of β-catenin to enhanced NSCLC cellular stemness, 25 which is suggested that EGFR signalling can drive β-catenin activation via various routes. In this study, we provide a novel F I G U R E 2 PRMT5 promotes cell proliferation in pancreatic cancer cells and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…IHC assays in chordoma tissues were performed and quantified according to our previous report . The degree of immunostaining of the indicated proteins was evaluated and scored by two independent observers as previously described, scoring both the proportions of positively stained tumor cells and their staining intensities.…”
Section: Methodsmentioning
confidence: 99%